Diabetes and Oral Health: Advancements in Prevention, Screening and Treatment of Periodontal Diseases - Anuj Singh Parihar; Sharika Gopinath; Manish Rathi; Mohammad Jalaluddin; Pradnya Rajendra Khatavkar; Rashmi Laddha (Wolters Kluwer Medknow Publications, 2024)
Diabetes is a pervasive metabolic disorder that notably impacts various body systems, including oral health. One of the critical manifestations of diabetes in oral health is its exacerbating effect on periodontal diseases. Recent advancements in the prevention, screening, and treatment of periodontal diseases have become increasingly significant due to the bidirectional link between periodontal health and diabetes management. This review explores contemporary strategies and technological innovations in the comprehensive management of periodontal diseases among diabetic patients. It highlights the integration of digital dentistry tools such as artificial intelligence (AI) and teledentistry in enhancing diagnostic precision and treatment outcomes. Preventive measures, including new pharmacological formulations and lifestyle interventions tailored for diabetic individuals, are discussed. Additionally, the review underscores the importance of routine screening protocols that incorporate glycemic control status to refine treatment plans for periodontal therapies. Furthermore, advancements in regenerative therapies, including the application of growth factors and stem cell therapy, are examined for their potential to restore periodontal tissue integrity, offering promising directions for future research and clinical practice. Through a synthesis of recent literature, this review aims to provide insights into effective periodontal disease management strategies that are critical for improving the overall health and quality of life of individuals with diabetes.